New Zealand ecosanctuaries: types, attributes and outcomes. Issue 3 (3rd July 2019) - Innes, John; Fitzgerald, Neil; Binny, Rachelle; Byrom, Andrea; Pech, Roger; Watts, Corinne; Gillies, Craig; Maitland, Matt; Campbell-Hunt, Colin; Burns, Bruce
ABSTRACT: We define an ecosanctuary in a New Zealand context as 'a project larger than 25 ha implementing multi-species, pest mammal control for ecosystem recovery objectives, and with substantial community involvement'. We present attributes of 84 projects meeting this definition, including three lacustrine islands, 16 marine islands, seven ring-fenced ecosanctuaries, seven peninsula-fenced ecosanctuaries and 51 unfenced mainland ecosanctuaries. Ecosanctuaries have biological and social objectives, and some have returned threatened, previously extirpated taxa to the New Zealand mainland. Increasingly, these intensively managed sites are being embedded in human-altered landscapes with low levels of pest control – a 'core and buffer' system. Most community groups that establish ecosanctuaries lack the technical expertise, resources and mandate to undertake regional or national prioritisation. There is a strong need for agency leadership of this, and to develop best practice pest control, pest monitoring and biodiversity outcome monitoring tools, as goals for national restoration of biodiversity rapidly expand.